Nettordbøker og Norsk Ordbok – hvordan etablere en vitenskapelig nettordbok - Ore, Christian-Emil (Nordiske Studier i Leksikografi, 2012)
Printed dictionaries have been the way of disseminating systematized information about the use and meaning of words. During the last three decades electronic dictionaries have been common. Most large online dictionaries are based on retro-digitization and are electronic replica of the originals. To defend the cost of converting the printed text to electronic text, the result should be more than an online reproduction. What exactly this ‘more’ should be is unclear. As a background some dictionaries are examined to show how the digital medium is exploited. In a paper in 1999 I described a meta-dictionary linking the entries with the source material as a future strategy for NO thus making the dictionary into an electronic scientific publication with reproducible results. In 2002 the meta-dictionary was redesigned to become a pivot in the new combined source database, text corpus and editing system for NO. Vols 5–12 are edited in the new system. The meta-dictionary and the linked sources have become a valuable repository. The bidirectional linking in the system makes each headword in a source an entry point to NO and the entire system, thus giving dialect users a unique opportunity to see their dialect in the larger context. The main objective of the NO project is the printed dictionary. However, the system is well prepared to meet the challenge when the ‘web ‘and ‘app’ age will soon make the online database the main access point.